Absence of both CD56 and CD117 expression on malignant plasma cells is related with a poor prognosis in patients with newly diagnosed multiple myeloma. (January 2016) - Pan, Ying; Wang, Huiping; Tao, Qianshan; Zhang, Cui; Yang, Dongdong; Qin, Hui; Xiong, Shudao; Tao, Lili; Wu, Fan; Zhang, Jiakui; Zhai, Zhimin
Highlights: Evaluating clinical values of CD56 and CD117 expression in MM patients. Expression of CD56 was associated with favorable response and OS. CD117 expression did not show association with favorable response and OS. Absence of both of CD56 and CD117 was associated with the poorest prognosis. Abstract: We retrospectively evaluated the association between the expression of CD56 and CD117 on neoplastic plasma cells and patients prognosis in 50 newly diagnosed multiple myeloma (MM) patients. The overall survival (OS) was measured and Cox proportional hazards model was used to evaluate CD56 and CD117 as possible prognostic factors for OS. CD56+ and CD117+ were detected in 74% and 32% multiple myeloma cases, respectively. In Kaplan–Meier analysis, CD56 and CD117 expression demonstrated potential prognostic impacts and were associated with longer OS (CD56: p  = 0.004, CD117: p  = 0.022), absence of both of them showed significantly shorter OS ( p  = 0.046 compared to CD56+/CD117+ group, p  = 0.014 compared to CD56−/CD117+ or CD56+/CD117− group). Multivariate analysis showed that CD56 was independently prognostic of longer OS ( p  = 0.012). After induction chemotherapy, overall response rates (ORR) was higher in CD56-positive group compared to CD56-negative group (70.6% versus 30.0%, p  = 0.024), however, there was no difference between CD117-positive and CD117-negative group (69.2% versus 58.1%, p  = 0.448). This study demonstrated the prognostic value of CD56 and CD117 in patients with newly diagnosed MM patients. Absence of both of them was associated with the poorest prognosis.